Isolation and Identification of Fungi from Bactrocera dorsalis as Candidate Entomopathogenic Fungi - Damayanti, Rizka Dwi; Emantis Rosa; Setiawan, Wawan Abdullah; Handayani, Tundjung Tripeni (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2024)
Cultivation of horticultural crops especially fruits, has long been practiced in Indonesia. Citrus plants are one of the main fruit commodities developed in Indonesia. Increased citrus production is inseparable from challenges, especially in controlling harmful pest attacks. Bactrocera fruit fly has attracted worldwide attention because of its ability to attack more than a hundred horticultural crops and cause crop failure. Various ways have been done to control Bactrocera, such as protecting the fruit with wrapping and even the use of synthetic insecticides that cause many losses. To overcome this, innovations are needed using biological control. Entomopathogenic fungi are potential candidates for bioinsecticides. This study aims to isolate and identify entomopathogenic fungi from Bactrocera dorsalis from citrus plants. The entomopathogenic fungus isolation method uses the moist chamber method. Then the fungal isolates will be identified macroscopically and microscopically. The isolation results show that five types of fungi are identified from the body of Bactrocera dorsalis. The five fungi can be used as candidates for entomopathogenic fungi.